How exposure to a neonicotinoid pesticide affects innate and learned close-range foraging behaviour of a classical biological control agent - Gabriele Rondoni; Elena Chierici; Elissa Daher; Franco Famiani; Jacques Brodeur; Eric Conti (Biological Control)
While foraging in agricultural habitats, natural enemies, such as egg parasitoids, may encounter insecticide residues, which, if not lethal, can alter host location behaviour and learning capacity. Such interference can reduce the potential of biological control agents, especially exotic species which are released in small numbers in a new environment and first need to establish and build up their populations. Several studies have investigated the lethal effects of pesticides on parasitoids, but less information is available about non-lethal consequences, and no information is available on the potential effect on associative learning in egg parasitoids. The egg parasitoid Trissolcus japonicus (Ashmed) (Hymenoptera: Scelionidae) is a biological control agent of the invasive brown marmorated stink bug, Halyomorpha halys (Stål) (Hemiptera: Pentatomidae). We hypothesised that a low concentration (causing 20 % parasitoid mortality) of a commonly used neonicotinoid insecticide (acetamiprid) alters the behaviour and learning capacity of T. japonicus to exploit the chemical traces left by reproductive females of either the main host, H. halys, or of an alternative host, Arma custos (F.) (Hemiptera: Pentatomidae). In open arena bioassays, parasitoid females responded positively to traces left by both stink bug species. Following oviposition experience and encounter with host traces (associative learning), T. japonicus reduced foraging time. Parasitoids previously exposed to neonicotinoid showed changes in foraging behaviour, with increased residence time spent in the host-contaminated area and altered kinetics of the walking behaviour. Neonicotinoid exposition did not affect the learning ability of parasitoid females 1 h after oviposition experience but prolonged the memory retention. The insecticide effects on female parasitoid behaviour may affect its reproductive ability and this should be considered when attempting its establishment in the introduction areas.